Penerapan Komunikasi Terapeutik Pada Proses Penyembuhan Pasien Di Bangsal Keperawatan RSUD Kota Semarang - Yularsih, Dinita (Jurnal The Messenger, 2014)
Dinita Yularsih. G.331.100.019. Application of Therapeutic Ccommunication in The Healing Process of Patients in Nursing Wards in General Hospitals Semarang Skripsi : Program S-1 Study of Communication Studies University of Semarang. This study aims to determine the effectiveness of the application of therapeutic communication in nursing wards General Hospital Semarang, and how much influence can give satisfaction to the customer as a hospital patient. The foundation of the theory used in this study is the theory of interpersonal communication, persuasive communication, symbolic interaction, and therapeutic communication. The research method used is the deskriptive qualitative.Teknique qualitative method of data collection is done by in-depth interviews and observation, data collection techniques by purposive sampling technique. This study involves a Physician Specialist, Head of Nursing, in patient room nurses, and hospital patients Semarang in accordance with the criteria previously specified writer. Concluded that therapeutic communication is applied by doctors and nurses in hospitals Semarang going very well on the healing process of the patient. Application not only in the nursing ward, but has started since the patient was still in the clinic. With the implementation of therapeutic communication is expected the patient will feel comfortable while undergoing treatment in hospital and were satisfied with the services provided by the hospital in Semarang.